Spectral-domain optical coherence tomography parameters associated with baseline vision in diabetic cystoid macular edema - Alfaran, Abdulrahman (2013)
Purpose to study spectral-domain optical coherence tomography (SD-OCT) parameters that may be associated with baseline visual acuity in eyes with center-involved diabetic cystoid macular edema (DCME) Methods The analysis included eyes with new onset center-involved DCME that had to have had a macular SD-OCT and fluorescein angiography (FA) at presentation. The baseline OCT scans were analyzed for the extent of retinal involvement by the cystoid change and its location with respect to the center. Both inner and outer retinal parameters were assessed. Eyes with clinical and angiographic evidence of lipid and ischemic maculopathy and those with poor quality OCT were excluded. Statistical analysis correlating the various OCT variables with baseline logMAR visual acuity was performed. Results Forty-nine eyes of 35 patients were analyzed. Twenty-five patients (71.4%) were males and 10 (28.6%) were females with a mean (±SD) age of 57.22 (±10.4) years (range 29 - 78 years). The baseline Log MAR visual acuity, central macular thickness (CMT) and central foveal thickness (CFT) ranged from 0.3 to 1.2; mean (±SD) = 0.53 (±0.23) (20/40 to 20/300 Snellen equivalent range), 315 to 738 microns; mean (±SD) = 462.3 (±106.1) microns and 153 to 735 microns; mean (±SD) = 442.3 (±137.5) microns respectively. Pearson correlation test showed that the only OCT parameters associated with the baseline visual acuity were the chord length of involvement of the photoreceptor IS/OS junction within the central subfield (CSF) (p=0.001), the thickness of the residual photoreceptor outer segments within the CSF (p=0.002), and the size of the largest cystoid space within the CSF (p=0.037). Conclusions In DCME, baseline visual acuity appears to correlate strongly with the status of the photoreceptor outer segments and to a lesser extent with the degree of cystoid change in the CSF. These findings may help explain the impact of specific morphological changes on visual acuity in eyes with center-involved DCME